2017
DOI: 10.1002/celc.201700776
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Na‐Storage Performance of a Nickel‐Based Ferricyanide Cathode in High‐Concentration Electrolytes for Aqueous Sodium‐Ion Batteries

Abstract: Nickel‐based ferricyanides have attracted much attention as cathode materials for aqueous sodium‐ion batteries, owing to their room‐temperature synthesis and open structural framework. However, factors affecting their electrochemical performance are still not clear. Herein, the effect of electrolyte concentrations on electrochemical properties of the ferricyanide cathode has been investigated by combining cyclic voltammetry, charge/discharge tests, and electrochemical impedance microscopy. It is found that hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…The high capacity retention of more than 90 % at 10 C relative to the capacity at 0.5 C suggests outstanding high‐rate capability. This is attributed to the unique open‐framework structure of Prussian‐blue analogues, which allows ultrafast charge‐transfer and ionic‐diffusivity ,. In addition, it renders excellent cycling performance (Figure b), with a capacity retention of 96 % after 1000 cycles at 10 C. Table compares the electrochemical performance of the cathode materials presented in this work and previous reports.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…The high capacity retention of more than 90 % at 10 C relative to the capacity at 0.5 C suggests outstanding high‐rate capability. This is attributed to the unique open‐framework structure of Prussian‐blue analogues, which allows ultrafast charge‐transfer and ionic‐diffusivity ,. In addition, it renders excellent cycling performance (Figure b), with a capacity retention of 96 % after 1000 cycles at 10 C. Table compares the electrochemical performance of the cathode materials presented in this work and previous reports.…”
Section: Resultssupporting
confidence: 51%
“…As reported, the electrochemical stability window of concentrated NaClO 4 electrolyte (17 mol Kg −1 ) can be widen to 2.8 V, which enables aqueous Na 2 MnFe(CN) 6 /NaTi 2 (PO 4 ) 3 battery working reversibly . The NaClO 4 electrolyte with concentrations of more than 6 M can achieve high‐efficiency Na‐storage performance of nickel‐based hexacyanoferrates . However, electrochemical properties of Ni‐substituted copper hexacyanoferrates in high‐concentration electrolytes are lack of being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that 35 M NaFSI‐based aqueous electrolyte showed a wide electrochemical window up to 2.6 V. 6 M NaClO 4 aqueous electrolyte enabled NaNi [Fe(CN) 6 ] exhibiting unexpectedly high initial Coulombic efficiencies of 99.3 % and excellent cycling stability with 96.3 % retention after 1000 cycles . Therefore, designing Ti substitution and high‐concentration electrolyte would be an effective strategy to reach excellent electrochemical performance of Na 3–x V 2–x Ti x (PO 4 ) 3 cathode for aqueous SIBs.…”
Section: Introductionmentioning
confidence: 96%
“…Electrolytes in SIBs can be generally classified into five common types: organic electrolytes, ionic liquids (ILs), aqueous electrolytes, solid polymer electrolytes, and inorganic solid electrolytes . Among these electrolytes, organic electrolytes, especially those based on esters and ethers, are the most commonly used electrolytes in SIBs, due to their merits of relatively high ionic conductivity as well as superior wettability toward both the porous separators and the electrodes.…”
Section: Introductionmentioning
confidence: 99%